Incidencia de astigmatismo y su relación con el rendimiento académico en estudiantes de 8vo, 9no y 10mo año de educación general básica de la Unidad Educativa Fiscal “Carlos Urgiles Gonzales” Cantón Guayaquil, junio-octubre 2023. - Guevara Alvarado, Isis Raquel (2024)
Incidences of astigmatism and its relationship with the academic performance of 8th, 9th and 10th year students of Basic General Education of the Fiscal Educational Unit ‘‘Carlos Urgiles Gonzales’’ Cantón Guayaquil, June – October 2023. Visual health difficulties have been increasing over time, due to various elements such as the internet with its social networks, cell phones, video games, etc. One of these complications is a defect in the curvature of the cornea or lens of the eye, which is understood as astigmatism. In this study, more information will be revealed about the characteristics of the eyeball and how to prevent astigmatism and take care of our visual health so that this refractive defect does not cause other pathologies that may affect our daily lives, through the correction of This problem, the students who benefit will also be able to learn about their refractive error and treat it with a health professional. The objective is to determine the degree of incidence of astigmatism in Basic General Education students of the Carlos Urgiles Gonzales Fiscal Educational Unit Canton Guayaquil, June - October 2023. This present research is field, analytical with a prospective cross-section and quantitative. It is made up of 240 8th, 9th and 10th grade students from the Carlos Urgiles Gonzales Fiscal Educational Unit and the sample was taken from 130 students and the degree of incidence of astigmatism and academic performance were determined, refractive defects were found through a visual examination. Surveys were also used to evaluate the statistics and obtain part of the results.